The 'community' in community case management of childhood illnesses in Malawi. Issue 1 (1st December 2016) - Zembe-Mkabile, Wanga Z.; Jackson, Debra; Sanders, David; Besada, Donela; Daniels, Karen; Zamasiya, Texas; Doherty, Tanya
Abstract : Background: Malawi has achieved a remarkable feat in reducing its under-5 mortality in time to meet its MDG 4 target despite high levels of poverty, low female literacy rates, recurrent economic crises, a severe shortage of human resources for health, and poor health infrastructure. The country's community-based delivery platform (largely headed by Health Surveillance Assistants, or HSAs) has been well established since the 1960s, although their tasks and responsibilities have evolved from surveillance to health promotion and prevention, and more recently to include curative services. However, the role of and the form that community involvement takes in community-based service delivery in Malawi is unclear. Design: A qualitative rapid appraisal approach was utilised to explore the role of community involvement in the HSA programme in Malawi to better understand how the various community providers intersect to support the delivery of integrated community case management by HSAs. Twelve focus group discussions and 10 individual interviews were conducted with HSAs, HSA supervisors, mothers, members of village health committees (VHCs), senior Ministry of Health officials, district health teams, and implementing partners. Results: Our findings reveal that HSAs are often deployed to areas outside of their village of residence as communities are not involved in selecting their own HSAs in Malawi. Despite this lack of involvement in selection, the high acceptance of the HSAs by community members and community accountability structures such as VHCs provide the programme with legitimacy and credibility. Conclusions: This study provides insight into how community involvement plays out in the context of a government-managed professionalised community service delivery platform. It points to the need for further research to look at the impact of removing the role of HSA selection and deployment from the community and placing it at the central level.